2018
DOI: 10.1038/s41467-018-04664-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustained SREBP-1-dependent lipogenesis as a key mediator of resistance to BRAF-targeted therapy

Abstract: Whereas significant anti-tumor responses are observed in most BRAFV600E-mutant melanoma patients exposed to MAPK-targeting agents, resistance almost invariably develops. Here, we show that in therapy-responsive cells BRAF inhibition induces downregulation of the processing of Sterol Regulator Element Binding (SREBP-1) and thereby lipogenesis. Irrespective of the escape mechanism, therapy-resistant cells invariably restore this process to promote lipid saturation and protect melanoma from ROS-induced damage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 67 publications
(65 reference statements)
1
90
1
Order By: Relevance
“…In line with this, acute treatment with vemurafenib or trametinib reduced transcript level of SLC7A11 in BRAF V600E melanoma cells [190]. Others have identified changes of the lipid metabolism, such as accumulation of PUFAs, in melanoma cells exposed to vemurafenib [191]. BAY 87-2243, an inhibitor that impairs OXPHOS by targeting the mitochondrial complex I, cooperated with vemurafenib in attenuation of melanoma tumor growth in vivo [187], although this could be related to induction of both ferroptosis and necroptosis as reported by others [152].…”
Section: Ferroptosis In Melanomamentioning
confidence: 68%
“…In line with this, acute treatment with vemurafenib or trametinib reduced transcript level of SLC7A11 in BRAF V600E melanoma cells [190]. Others have identified changes of the lipid metabolism, such as accumulation of PUFAs, in melanoma cells exposed to vemurafenib [191]. BAY 87-2243, an inhibitor that impairs OXPHOS by targeting the mitochondrial complex I, cooperated with vemurafenib in attenuation of melanoma tumor growth in vivo [187], although this could be related to induction of both ferroptosis and necroptosis as reported by others [152].…”
Section: Ferroptosis In Melanomamentioning
confidence: 68%
“…Previous reports have shown that fatostatin inhibits proliferation and induces apoptosis in ER+ breast cancer cells via the activation of endoplasmic reticulum (ER) stress and lipid accumulation, under lipid-sufficient conditions [47]; this could be attributed to the fact that fatostatin directly and negatively impacted on the lipid-synthesis and metabolic pathways [48]. This is supported by a previous study where ectopic expression of SREBP1 resulted in increased levels of lipogenic genes, such as fatty acid synthase (FASN), stearoyl CoA desaturase (SCD), and acetyl-CoA carboxylase-1 (ACC), and augmented lipogenesis and sphere formation in MCF10A stem-like cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…The short-lived anti-cancer effects noticed in BRAFV600E-mutant metastatic melanoma treated with BRAF inhibitors are good examples [169,170]. According to Talebi et al (2018) [171] the lipogenic pathway, mediated by Sterol Regulatory Element Binding Protein (SREBP-1) is culpable in oncogenic BRAF constitutive activation and instrumental to therapy resistance. SREBP-1 inhibitors together with BRAF inhibitors should be adopted to defeat resistance to BRAFV600E-targeted therapy [171].…”
Section: Resistance To Braf-targeted Therapymentioning
confidence: 99%